Magnetic micro-device for manipulating PC12 cell migration and organization1. Issue 9 (7th May 2015) - Alon, N.; Havdala, T.; Skaat, H.; Baranes, K.; Marcus, M.; Levy, I.; Margel, S.; Sharoni, A.; Shefi, O.
<x xml:space="preserve">Abstract</x> A ferromagnetic micropatterned device generating highly localized magnetic fields with controllable magnetic flux densities to manipulate neuron-like cell migration and organization at the microscale level.